Genetic mapping using genotypingbysequencing in the clonally propagated cassava - Rabbi, Ismail Y.; Hamblin, M.; Gedil, Melaku A; Kulakow, Peter A.; Ferguson, Morag E.; Ikpan, A.; Ly, D.; Jannink, Jean-Luc (Wiley, 2014)
Cassava (Manihot esculenta L.) is one of the most important food crops in the tropics, but yields are far below their potential. The gene pool of cassava contains natural genetic diversity relevant to many important breeding goals, but breeding progress has been slow, partly because of insuf-ficient genomic resources. As a first step toward implementing genomewide genetic studies that will facilitate rapid genetic gain through breed-ing, we genotyped-by-sequencing a set of 182 full-sibs population of cassava that segregated in several traits: resistance to the cassava mosaic disease (CMD) and yield under CMD pressure; increased carotenoid content in storage roots; color of stem exterior and anthocyanin pigmen-tation in the petioles, inner root skin, and api-cal leaves. Employing a rare-cutting restriction enzyme, PstI, in a genotyping-by-sequencing (GBS) library preparation, we obtained 2478 segregating single nucleotide polymorphisms (SNPs), of which 1257 passed standard filter-ing for missing genotypes and deviation from expected genotypic frequencies. We mapped 772 SNPs across 19 linkage groups and anchored 313 unique scaffolds from the version 4.1 of the cassava genome assembly. Most of the stud-ied morphological traits as well as resistance to CMD and root carotenoid content showed quali-tative inheritance. As expected, quantitative trait loci analysis for these traits revealed single loci surrounded by small confidence intervals. Yield under CMD was associated with the CMD resis-tance locus. We show that GBS is a powerful genotyping tool that provides a sufficient number of markers for unraveling the genetic architecture of Mendelian traits in cassava in addition to the development of a robust genetic map that can help anchor unassembled genomic scaffolds.